Campylobacter jejuni Outer Membrane Vesicles Play an Important Role in Bacterial Interactions with Human Intestinal Epithelial Cells - Elmi, Abdi (American Society for Microbiology, 2012)
Campylobacter jejuni is the most prevalent cause of food-borne gastroenteritis in the developed world; however, the molecular basis of pathogenesis is unclear. Secretion of virulence factors is a key mechanism by which enteric bacterial pathogens interact with host cells to enhance survival and/or damage the host. However, C. jejuni lacks the virulence-associated secretion systems possessed by other enteric pathogens. Many bacterial pathogens utilize outer membrane vesicles (OMVs) for delivery of virulence factors into host cells. In the absence of prototypical virulence-associated secretion systems, OMVs could be an important alternative for the coordinated delivery of C. jejuni proteins into host cells. Proteomic analysis of C. jejuni 11168H OMVs identified 151 proteins, including periplasmic and outer membrane-associated proteins, but also many determinants known to be important in survival and pathogenesis, including the cytolethal distending toxin (CDT). C. jejuni OMVs contained 16 N-linked glycoproteins, indicating a delivery mechanism by which these periplasm-located yet immunogenic glycoproteins can interact with host cells. C. jejuni OMVs possess cytotoxic activity and induce a host immune response from T84 intestinal epithelial cells (IECs), which was not reduced by OMV pretreatment with proteinase K or polymyxin B prior to coincubation with IECs. Pretreatment of IECs with methyl-beta-cyclodextrin partially blocks OMV-induced host immune responses, indicating a role for lipid rafts in host cell plasma membranes during interactions with C. jejuni OMVs. OMVs isolated from a C. jejuni 11168H cdtA mutant induced interleukin-8 (IL-8) to the same extent as did wild-type OMVs, suggesting OMV induction of IL-8 is independent of CDT.